Crop science : progress and prospects - Nösberger, J. (Josef); Geiger, H. H. (Hartwig H.); Struik, P. C. (Paul Christiaan), 1954- (Cabi Ser., 2001)
This text includes keynote invited papers from the Third International Crop Science Congress held in Hamburg, Germany in August 2000. The papers provide an overview of the major issues confronting crop science today and in the future.